Regulation of the MiTF/TFE bHLH-LZ transcription factors through restricted spatial expression and alternative splicing of functional domains - Kuiper, Roland P. (Oxford University Press, 2004)
The MiTF/TFE (MiT) family of basic helix–loop–helix leucine zipper transcription factors is composed of four closely related members, MiTF, TFE3, TFEB and TFEC, which can bind target DNA both as homo- or heterodimers. Using real-time RT–PCR, we have analyzed the relative expression levels of the four members in a broad range of human tissues, and found that their ratio of expression is tissue-dependent. We found that, similar to the MiTF gene, the genes for TFEB and TFEC contain multiple alternative first exons with restricted and differential tissue distributions. Seven alternative 5′ exons were identified in the TFEB gene, of which three displayed specific expression in placenta and brain, respectively. A novel TFEC transcript (TFEC-C) encodes an N-terminally truncated TFEC isoform lacking the acidic activation domain (AAD), and is exclusively expressed in kidney and small intestine. Furthermore, we observed that a considerable proportion of the TFEC transcripts splice out protein-coding exons, resulting in transcription factor isoforms lacking one or more functional domains, primarily the basic region and/or the AAD. These isoforms were always co-expressed with the intact transcription factors and may act as negative regulators of MiTF/TFE proteins. Our data reveal that multiple levels of regulation exist for the MiTF/TFE family of transcription factors, which indicates how these transcription factors may participate in various cellular processes in different tissues.